Integrative Critical Analysis of Multidisciplinary Operations in Medical Clinics: Exploring the Interplay Between Departments for Optimal Patient Care - M Albaqami , Faris Mohsen; Alqahtani , Abdulmohsen Abdullah J; Alateeq , Esam Saad Moh; Alzaidi , Yazeed Abdulhadi Safran; Ayashi, Hussain Bahlool Hussain; Alqarni, Mohammad Najem Mohammad; Alomari , Abdullah Mofareh Yahya; Alshehri, Saeed Abdullah; Alotaibi, Nahar Ali; Alqahtani , Athbah Hamad (Journal of Ecohumanism, 2024)
This article critically examines the multidimensional operations within medical clinics, focusing on the intricate interplay between key departments such as nursing, pharmacy, laboratory, radiology, and administration. It highlights the essential role of interdisciplinary collaboration in achieving optimal patient outcomes and addressing the challenges posed by departmental silos, miscommunication, and resource allocation inefficiencies. Drawing on existing literature and best practices, the study identifies strengths and weaknesses in current operational frameworks while exploring innovative opportunities for integration, including the use of technology, team-based care models, and automation. Recommendations are provided to enhance interdepartmental coordination, promote patient-centered care, and improve the overall efficiency and effectiveness of medical clinic operations.